Penggunaan Diksi dalam Komik Ugly Duckling Become Swan Karya Hwang Mi Ree Terjemahan Dwita Rizki Nientyas - Bella Novera; Sudirman Shomary (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to describe and analyze the use of diction in the form of changes in meaning and the use of onomatopoeias contained in the comic Ugly Duckling Become Swan by Hwang Mi Ree, translated by Dwita Rizki Nientyas. The method used in this study is descriptive analytic method with a research technique, namely the hermeneutic technique. Based on the research conducted, it can be concluded that (1) the changes in meaning found in the comic Ugly Duckling Become Swan by Hwang Mi Ree, translated by Dwita Rizki Nientyas, include: a) changes in the meaning of expanding meaning such as brother, , breaking up, bandar, b) changes in the meaning of narrowing meanings such as cigarettes, c) changes in meaning of amelioration such as man, wife, d) changes in meaning of pejoration such as pigs, women, e) changes in meaning of metaphors such as geese, wolves, f) changes in meaning of metonymy such as Christmas, champagne, (2) the use of onomatope found in the comic Ugly Duckling Become Swan by Hwang Mi Ree translated by Dwita Rizky Nientyas, including a) onomatopoeic animal sounds such as "Meow!", "Grrrrrh!", b) onomatopoeic human voices such as "Hahaha!", "Phew", "Hihihi ”, c) onomatopoeic sounds of other objects such as “Trak set”, “Duakh”.